Butorphanol dependence in a health-care professional: A case report with narrative review. (3rd September 2019) - Chattopadhyay, Ankita; Gupta, Snehil; Dayal, Prabhoo; Mandal, Piyali; Agrawal, Alok; Ambekar, Atul
ABSTRACT: Prescription opioids' use are very prevalent worldwide. Butorphanol, one of the prescription opioid, is frequently used as an opioid analgesic especially in the peri-operative period. However, there are few case reports which highlight about the dependence potential of butorphanol. The available literature on butorphanol dependence have mostly reported about its physical nature of dependence. In this report, we intend to present a case of a health care professional who was suffering from butorphanol dependence. Contrary to previous reports, in the current case the primary reason for using butorphanol (intramuscular) was to experience the euphoria. The client was detoxified with the Buprenorphine (sublingual) in an in-patient setting following which he was started on oral Naltrexone (opioid antagonist) as a form of long term maintenance. The current report highlights about the addiction potential of butorphanol, which can be attributed to its euphoric effect. It also observes that the health care professionals are the vulnerable group in terms of becoming dependent on prescription opioids. Further, the report emphasizes the need of the judicious use of prescription opioids (including butorphanol) by the health care professionals and also to effectively regulate it.